Representations of the Police in Contemporary Russian Police TV Series: The Case of Glukhar'. (April 2016) - Khitrov, Arseniy
This article answers the question of how contemporary Russian TV series portray the police. The results derive from a single-case thematic and functionalist study of the popular Russian TV series Glukhar' (which aired from 2008 to 2011). The show merits special attention because it was on air when the Russian police were undergoing a legitimacy crisis, which lead to the 2009 police reform. The series recognized the crisis and responded to it with a set of justifications. I analyze the show's social and cultural contexts, its plot patterns, and the functions of its characters. I build a typology of justifications and claim that the show justifies the police through an open discussion about the reasons for and consequences of their lawlessness. The series shows that the legitimacy of the police is repeatedly questioned, but trust in the police is always restored because police officers are depicted as estranged from the state but not from the community. Thus, the show contains an interesting example of overcoming a legitimacy crisis through its recognition. The study opens the floor to further discussions about how popular culture resolves intense social debates about policing by symbolic means in a moment when police legitimacy is contested.